An archival feminist pedagogy: unlearning and objects as affective knowledge companions. Issue 3 (3rd May 2016) - Perrier, Maud; Withers, Deborah
Abstract: This paper is based on workshops conducted with students at Bristol University with some of the materials from the Feminist Archive South. We explore how the sensory wonder of the archives enriched and reshaped the practice of feminist pedagogy especially with regard to the interface between ontology and epistemology. We argue that the feminist archive is an important resource which incites us to shift our focus on the process of knowledge production as stories encountered in the archive can challenge the authority and coherence of dominant feminist stories. This can produce feelings of disorientation which act as important moments through which different kinds of feminist knowledge can emerge. Our approach places feelings at the centre of encounters with knowledge because of the mutual entanglement of thinking and feeling rendered salient in the feminist archive. Finally, these processes facilitate different kinds of student–teacher collaboration, with students positioned as co-researchers working to document and interpret the feelings, knowledge and transformations that emerge from the encounter-with the feminist archive. The objects we encountered worked as knowledge companions to stimulate collaborative (un)learning and to produce unique forms of affective knowledge.